Analysis of Phasor Measurement Units for Optimal Placement using Particle Swarm Optimization and Sam ACO Algorithm - Babu, M.Naveen; Dhal, P.K. (2021 Asian Conference on Innovation in Technology (ASIANCON), 2021)
The Phasor Measurement Unit (PMU) is an important instrument for power system monitoring and control. It provides continuous, synchronized voltage measurements at the buses, as well as current stage esteem for such buses in which this PMUs can be found. The aim of the best possible PMU location (OPMUL) problem is to choose a small number of PMUs that will allow the entire network to be visible. To solve the optimal PMU placement (OPMUP) problem, several meta-heuristic optimization methods have been proposed. The proposed description is put to the test on IEEE 14 test systems, and the findings for full observability of the system under normal conditions are presented in this paper. In IEEE 14 bus systems, the proposed PMU placement has been tested.